The effects of taste sensitivity and repeated taste exposure on children's intake and liking of turnip (Brassica rapa subsp. rapa); a bitter Brassica vegetable (IR) - Nurfarhana Diana Mohd Nor (2018)
Taste sensitivity plays an important role in influencing food preferences and thus nutritional status. It has been reported that children have low vegetable consumption. Differences in bitter taste sensitivity between individuals may influence vegetable consumption, especially Brassica vegetables. Glucosinolates (GSLs) are present in high amount in Brassica vegetables, and these compounds contain a thiourea group, which is partly responsible for the bitter taste of Brassica vegetables. The thiourea group also exists in 6-propylthiouracil (PROP), and the ability to taste it is genetically determined. Variations in the bitter taste receptor of TAS2R38 predominantly explain the differences in response of PROP perception. Additionally, phenotypic measure of fungiform papillae density (FPD) has been shown to contribute to taste sensitivity, and gustin (CA6) gene has been proposed to be involved in the development of papillae. Existing literature has shown that repeated taste exposure can modify the acceptance of initially disliked/novel foods However, no previous stuffy has considered taste sensitivity within a repeat taste exposure study design. The main objective of this thesis was to investigate the effects of taste genotypes (TAS2R38 and CA6) and phenotypes (PROP taster status and FPD) on the effectiveness of repeated taste exposure of an unfamiliar Brassica vegetable (turnip) on intake and liking in children aged 3 to 5 years . To support this main objective, we also determined the effects of cooking method on the sensory profile and consumer liking of turnip, and identified and quantified GSLs in turnip. Using parental reported questionnaires about children's preferences, this thesis also explored whether taste sensitivity would have effects on overall vegetable intake and liking in children. Our findings revealed that turnip liking is dependent on cooking method, where we found that roasted-turnip was the most preferred, and boiled-pureed turnip was the least preferred. Sweetness in turnip increased liking, while bitterness decreased liking. Although TAS2R38 genotype had a significant impact on bitter perception in turnip, where the PAV/PAV consumers tended to score higher bitter intensity than the PAVIAVI and AVI/AVI consumers, it did not influence taste liking. Our chemical analysis showed that there were 12 individual GSLs found across our turnip samples. Gluconasturtiin was the most abundant GSL, and we found significant differences in individual GSL content (except glucoalyssin) between samples. As expected, GSLs were positively correlated with bitter taste, and negatively correlated (except glucobrassicanapin) with sweet taste. In our main study, intake and liking of steamed-pureed turnip significantly increased after exposure, but there were no significant effects of taste genotypes and phenotypes. Furthermore, we found significant increases in intake and liking of the vegetable at follow-up, compared to pre-intervention. From the parent-reported questionnaires, we found no significant effects of taste genotypes and phenotypes on intake of vegetables collectively (Brassica, non- rassica and tal vegetables). However, there were some significant effects of these genotypes and phenotypes on intake of certain vegetables. For liking, FPD was found to have had a significant impact on Brassica and total vegetables where the low and high FPD groups had higher liking than the medium FPD group. From the questionnaire results, we concluded that vegetable intake and liking were positively correlated, suggesting that as intake increases, liking increases and vice versa. In conclusion, cooking method predicts turnip liking, and 12 GSLs in turnip were positively correlated with bitterness . Repeated taste exposure is effective in increasing the acceptance of an unfamiliar bitter vegetable in children, and has long-term positive effects. Taste sensitivity did not have a significant impact on the effectiveness of repeated taste exposure. However, there were significant effects of taste genotype (TAS2R38) and phenotypes (PROP taster status and FPD) on intake of specific vegetables, and only FPD influenced parent- reported liking of vegetables from the 3 to 5 year-old children.